Video-Biomechanical Analysis of the Shoulder Kinematics of Impact from Sode-Tsurikomi-Goshi and Tsurikomi-Goshi Judo Throws in Elite Adult Judoka - Maria Pantelidou; Wiesław Błach; Łukasz Rydzik; Tadeusz Ambroży; Ruqayya Lockhart; Manuela Angioi; Krzysztof Sokołowski; Nikos Malliaropoulos (Applied Sciences)
Background: The aim of this study was to calculate and compare the peak acceleration and peak negative velocity of uke’s shoulder during the course of two judo throwing techniques, Sode-Tsurikomi-Goshi (STG) and Tsurikomi-Goshi (TG). Methods: This study recruited male adult elite judo players with a mean age 26.5 of (SD = ±8.916), a minimum black belt ranking, and no injuries in the past six months. Participants were selected from the Aris Judo Club, Thessaloniki, Greece, ensuring high-level technique for safe and reliable outcomes. Informed consent was obtained. A Huawei 5T with a 48-megapixel camera was used to record the throws. Kinovea (version 0.8.15) software was used for two-dimensional motion analysis of shoulder displacement during throws and IBM SPSS Statistics (version 25.0, Armonk, NY, USA) with Microsoft Excel were used for the statistical analysis of the data. Results: The peak acceleration of uke’s shoulder during STG was lower than in the case of TG, but the statistical test did not confirm this difference (p = 0.1). The mean peak negative velocity of uke’s shoulder in TG was higher compared to STG, and this difference was statistically significant (p = 0.04). The test–retest reliability of STG throws was good (ICC = 0.74), and for TG throws, it was moderate (ICC = 0.60). The effect size was large for negative velocity in TG (d Cohen = 1.12) and moderate for acceleration in STG (d Cohen = 0.43). The individual test did not show a statistically significant difference between STG and TG (p = 0.2). Conclusions: A statistically significant difference in peak negative velocity in TG compared to STG would reveal that uke is thrown quicker by tori. Further research on impact forces to determine the effective mass of uke’s shoulder is advised.